If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2 * -8) + 3 = 15 Multiply 2 * -8 6(-16) + 3 = 15 Multiply 6 * -16 -96 + 3 = 15 Combine like terms: -96 + 3 = -93 -93 = 15 Solving -93 = 15 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 4w+15=91 | | 4(y+2)=5 | | -30=-2v | | 11x-45=-12 | | 8(x-1)+2(x-1)=90 | | -50+x+x+x=-11 | | ab=3x+12 | | 4c-5c+8.4=3.6-2c-4.2 | | 63=3v | | 87+x=120 | | -45+x=-31 | | 4+6x=7+2x | | -2(-3x+2)=-6 | | 3(2b-4)=5(b+2) | | 105x^2-182x+56=0 | | 7a+8=8a-2 | | 3(4x+7)+9(x-1)=180 | | 3x-5-4x=6-2x | | s+1.2=-.2 | | 107-2x=25x+23 | | 3x-2=3(x-0.6666666666666666) | | x^4+12x^2-27=0 | | 63y-42=64y | | 7x-1+22(x-1)=180 | | 6(x-4)+9=2x+4(-3+x) | | 3x^3-8x^2+4x=0 | | 5x+3y+12x-7xy= | | 16=1d+6 | | 4x+8+2x=5x-1 | | -4x^2-6x+4=0 | | 5x+3+6x-1=90 | | 4p-3q+7p-2q= |